Photoresponsive Binding Dynamics in High‐Affinity Cucurbit[8]uril‐Dithienylethene Host‐Guest Complexes. Issue 37 (29th May 2021) - Colaço, Miriam; Máximo, Patrícia; Jorge Parola, A.; Basílio, Nuno
Abstract: The use of external stimuli to control the binding kinetics in supramolecular systems is of critical importance for the development of advanced molecular machines and devices. In this work, a study focused on the kinetics of a water‐soluble host‐guest system based on cucurbit[8]uril and two dithienylethene (DTE) photoswitches is reported. It is shown that for the DTE guest comprising two anionic sulfonate side arms appended to pyridinium moieties, the formation/dissociation of the pseudorotaxane structures is slowed down by more than 100000‐fold with respect to its bipyridinium analogue. The decrease in ingression rate leads to the emergence of a competitive metastable product with the open DTE isomer that has an important influence in the overall binding kinetics. Moreover, the host‐guest dissociation kinetics is demonstrated to be approximately 100‐fold slower for the closed DTE isomer (t1/2 =107 h vs. t1/2 =1.2 h for the open isomer) allowing control over the dissociation rate with light. Abstract : Kinetic studies on host‐guest systems based on cucurbit[8]uril and dithienylethene (DTE) photoswitches shows that the more tightly bound closed DTE isomers are kinetically more stable that their open counterparts. This allows for the modulation of their binding dynamics with light stimulus constituting an attractive tool for the development of out‐of‐equilibrium supramolecular systems.